Purchasing power parity : the empirical case study of Zimbabwe - Magombo, Terrence (My University, 2022)
The study of Purchasing Power Parity (PPP) theorem and its geographical validity has gained a lot of attention lately among economists in a bid to solve the currency exchange puzzle. This paper looks into how the concept of PPP was formerly used in the case of Zimbabwe in estimating the inflation rate in 2008, one of the worst economic years of Zimbabwe, when the Country officially stopped issuing the nationwide headline inflation data. In 2008 Zimbabwe recorded the second highest ever reached inflation figure known to mankind, just behind Hungary in world history. The estimated yearly inflation figure in November 2008 was nearly 100 billion percent with a daily inflation rate of 98%. That means prices in general, including those on many essential items like goods and basic services, almost doubled every day. The government through the Central Bank printed notes in huge amounts. In this environment, the government stopped issuing official statistics figures creating a gap which was detrimental to the business world and the general public. A university professor, namely Steve Hanke, attempted to calculate the relative purchase power parity using a company’s share prices in different markets. Old Mutual plc was a company whose stocks were listed on the London Stock Exchange and Zimbabwe Stock Exchange. He used the fungibility of the stock to calculate the PPP against the USD and came up with a rate called Old Mutual Implied Rate (OMIR). In 2009 the economy was dollarized bringing stability and for a while the use of the OMIR was suspended. However, in 2016 the OMIR was back again and used by investors and in the parallel market. The government accused the parent company of manipulating exchange rate through its proxy the OMIR. This paper tests the validity of PPP for 2018 and 2019 to see if the concept was valid for Zimbabwe or not using the absolute and real exchange rate versions. There are three hypothesis tests conducted in this research: these are namely the 1) Multicollinearity test ii) Serial Correlation test and iii) Stationarity and cointegration tests. The model showed that there was no multicollinearity. However, the pure APPP proved to be autocorrelated and the AR (1) model was used to resolve the error. After the new lagged variable was introduced, there was no serial correlation in the new model. Applying the stationarity test the variables seemed to be all nonstationary. Commonly among econometricians would be to include the first differences in the model but however in this paper before we could do that cointegration test was used to see if the variables were cointegrated or not. The cointegration test showed that the variables were cointegrated. This means the model was not a spurious regression equation and was valid in the long-run. This paper concluded thus that PPP theorem was valid for Zimbabwe in the period selected and that the government had no economic basis to refute the OMIR.

Satın Alma Gücü Paritesi (Purchasing Power Parity ya da kısaca PPP) ve bu paritenin coğrafi geçerliliği son zamanlarda iktisatçılar arasında döviz mübadelesi sorunu çerçevesinde yoğun ilgi çekmiştir. Bu çalışma PPP yaklaşımının daha önceden 2008 yılında Zimbabve’de enflasyon tahmini için nasıl kullanıldığına odaklanmaktadır. 2008 yılı Zimbabve ekonomisi için en kötü yıllardan biri olmuş, ülkede enflasyon rakamlarının yayınlanmasından vazgeçilmiştir. 2008’de Zimbabve tarihte Macaristan’ın ardından bilinen ikinci en yüksek enflasyon artış oranı rakamına ulaşmıştır. Kasım 2008 için tahmin edilen yıllık enflasyon oranı yüzde 100 milyar iken günlük enflasyon %98 olmuştur. Bunun anlamı hemen hergün fiyatlar genel seviyesinin, gıda ya da temel hizmetlerin fiyatları gibi önemli fiyatlar da dahil olmak üzere, hemen hemen iki katına çıkmasıdır. Hükümet, merkez bankası eliyle, büyük miktarlarda para basmak durumunda kalmıştır. Böyle bir ortamda hükümet hem kamu hem de iş dünyası açısından oldukça yaşamsal bir boşluk yaratacak olmasına ragmen enflasyon rakamlarını resmen açıklamayı durdurmuştur. Steve Hanke ismindeki bir üniversite profesörü göreli satin alma gücü paritesi yaklaşımıyla bir şirketin farklı ülkelerdeki hisse fiyatlarını kullanarak enflasyon tahminine yönelmiştir. Old Mutual Plc. Hisseleri hem İngiltere’de Londra borsasında hem de Zimbabve’de Zimbabve borsasında kote edilmiş bir şirkettir. Hisse senetlerinin takas edilebilirliğinden yararlanılarak ABD Doları üzerinden PPP yaklaşımı tahminiyle bir Old Mutual Zımni Oranı (OMIR) elde edilmiştir. 2009 yılında ülke ekonomisi dolarize olduğundan ötürü OMIR’in kullanımı havada kalmıştır. Ancak, 2016’da OMIR hem resmi olmayan piyasalarda hem de yatırımcıların kendi aralarında tekrardan yaygın bir biçimde kullanılmaya başlanmıştır. Hükümet OMIR üzerinden manipülasyon yapıldığı iddiasıyla bu zımni oranın referanslamada kullanılmasına karşı çıkmaktadır. Bu çalışma PPP’nin geçerliliğini Zimbabve için 2018 ve 2019 yıllarını kullanarak hem mutlak hem de göreli PPP yaklaşımları üzerinden test etmektedir. Bu çalışmada üç hipotez testine yer verilmiştir. Bunlar çoklu eşyönlülük, seri korelasyon ile durağanlık ve koentegrasyon testleridir. Modelde çoklu eşyönlülük durumu saptanmamıştır. Ancak mutlak PPP modelinin temel kurulumunda seri korelasyona denk gelindiği için bir gecikmeli otoregresif bir terimle düzeltmeye gidilmiştir. Modellerde kullanılan değişkenler durağan değildir ancak koentegre oldukları saptanmış ve hata düzeltmesi yapılarak modellemeye devam edilmiştir. Model tahminleri neticesinde Zimbabve için el alınan dönemde PPP yaklaşımının enflasyonun zımni tahmini için kullanılabileceği, OMIR’in kullanımına karşı resmi söylemin bu çerçevede temelsiz olduğu saptanmıştır.
Keywords: arbitrage; Finance; foreign currency; foreign currency regimes doviz; Fungibility; Maliye; Purchasing power; Satın alma gücü; volatility; Zimbabwe